Simulation of counter drugs operations based on geospatial technology for use in a military training simulator. (2018) - Robert, Ornprapa P.; Kumsap, Chamnan; Janpengpen, Ampun
This article reports the adoption of potential surface analysis (PSA) to model drug trafficking routes in Thailand for military training scenarios of a small-arms simulator. GIS data layers were used for analytic hierarchy process. Experts were gathered to brainstorm for potential factors and their ratings based on knowledge, expertise and judgments. Physical, drug-aspect and socio-demographic factors were main factors and further separated into sub-factors. The consistency ratio (CR) was calculated at 0.09, the significance of the factors became less than 0.10, making the consistency acceptable. The PSA revealed potential drug-trafficking routes that were cross-checked with genuine routes. The created military training scenarios were validated by experienced military and security officials. The averaged satisfaction of 3.92 with the standard deviation of 0.75 confirms that the integrated methodology of modelling drug trafficking routes using potential surface analysis is another optional approach to upgrade the military small-arms training simulator.